Zi-Quan Liu*, Fang-Jun Kan, Shuang-Xin Xu, Rui-Cui Liu and Fu-Yi Jiang - Ning, X.Q.; Qiao, W.W.; Zhang, L.; Gao*, X. (Asian Journal of Chemistry, 2013)
There is a wide use of nano-ferric oxide. There are many ways to prepare iron oxide nano-particles, such as co-precipitation, micro-emulsion, sol-gel process, pyrolytic process, hydro-thermal method, forced hydrolysis, etc. This article started from the descriptions of the methods to prepare iron oxide nano-particles, emphasized on summing up the progress in the research on the preparing methods and technical part of nano-ferric oxide. This article also commented on the advantages and disadvantages of each method. It finally predicted the future of the trend of the research on the preparing methods of nano-ferric oxide.